Wirkung einer Feiertagsbereinigung des Länderfinanzausgleichs: eine empirische Analyse des deutschen Finanzausgleichs - Michael Broer (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In the German system of fiscal equalization Länder (States) with tax revenue below the average get payments from the Länder above the average. The difference between the average and the own tax revenue per capita will be compensated up to 75%. To prevent Länder from getting payments form other Länder by lowering their own tax rates and to get the right information about their ability to pay, the revenue of taxes with taxing autonomy is standardized. But Länder could also influence their tax revenues by the number of holidays, each Land decides on its own. A Land with many own holidays will get lower tax revenues and higher payments in the fiscal equalization system than the same Land with no extra holidays. To collect the real ability to pay of the Länder in the fiscal equalization system, it is necessary to eliminate the effect of the different number of holidays, too. This paper shows an approach to neutralize this effect, calculates its impact to the payments of each Land in the fiscal equalization system and presents some possible reaction of the Länder.
Keywords: H70; H71; H77; 330; tax autonomy; fiscal equalization; number of holidays in each State; micro simulation; Horizontaler Finanzausgleich; Zeit; Steueraufkommen; Ländersteuer; Gewerbesteuer; Deutschland